Spatiotemporal characteristics and multi-scenario simulation of territorial space carbon sink conflicts in the Sichuan-Yunnan ecological barrier region, China - Weijie Li; Yong Wang (Environmental and Sustainability Indicators)
Scientific evaluation and simulation of territorial space carbon sinks conflict (TSCSC) is an effective way to identify the regional carbon balance. However, previous research mainly focuses on the measurement, dynamic characteristics and driving factors of the current carbon sink, seldom considers the impacts of the future territorial space conflict on the carbon sink, especially in ecologically fragile areas. Thus, taking the Sichuan-Yunnan ecological barrier area as an example, this paper constructed a TSCSC evaluation model from the three dimensions of spatial carbon emission pressure, spatial carbon storage capacity and spatial instability, then analyzed the spatiotemporal evolution of TSCSC from 2000 to 2020 and its relationship with land use change, finally simulated and identified the degree of TSCSC and its potential risk areas under four scenarios in 2050 by applying the patch-generating land use simulation (PLUS) model. The study found that (1) the level of TSCSC gradually decreased from 2000 to 2020, and showed a spatial pattern of declining from the northeast to the southwest. (2) The rising areas of the TSCSC were clustered in the hilly areas of the northwest and the urban-rural interface of Chengdu, which is derived from cultivated land reclamation and urban land expansion. (3) In 2050, the carbon emission reduction scenario had the lowest the TSCSC value, which is regarded as the optimal model for alleviating the coercive effect of spatial conflicts on carbon balance. The study can offer a practical guidance for the mitigation of carbon sink conflict in ecologically fragile areas.